POLA MEDIASI DALAM PERSPEKTIF HUKUM ADAT - Mayastuti, Anti (Fakultas Hukum Universitas Sebelas Maret, 2013)
Indonesia is a country that has a value of harmony, tolerance, and communalism precedence over the values ââof individualism, therefore the type of dispute resolution further highlight the type of win-win solution compared disputes through litigation. The concept of dispute resolution through mediation using the principle of win-win solution in fact has been recognized in local community life traditional or indigenous people of Indonesia. The main characteristic of the mediation process is essentially the same as the negotiation process of deliberation or consensus. Mediation is not the best option to resolve the dispute, but as a goal in dispute with deliberation and consensus approach, the relationship between the two parties to the dispute to be maintained, so as to create social harmony.